The manga guide to statistics - Takahashi, Shin (Manga guide series., 2009)
Uses manga characters to introduce the reader to the world of statistics. Rather than learning from a dry textbook, readers follow the animated adventures of Rui and her teacher, Mamoru Yamamoto, as Rui interacts with a colorful cast of characters. The book consists of seven chapters, each containing a cartoon, text to supplement the cartoon, an exercise and answer section, and a summary. Readers learn about working with numerical and categorical data; probability; relationships between two variables; tests of independence; even how to perform calculations in Microsoft Excel.